Features of Microstructure and Percolation Behavior of Polypropylene Glycol, Filled by Multiwalled Carbon Nanotubes - E.A. Lysenkov; V.V. Klepko; I.P. Lysenkova (Журнал нано- та електронної фізики)
The research of the microstructure features, percolation behavior and impedance of systems based on polypropylene glycol and multiwalled carbon nanotubes (MWCNTs) is conducted using the methods of optical microscopy and impedance spectroscopy. It is set that in the investigated systems the typical percolation transition is observed at some threshold MWCNTs concentration (0.45 %). The fractal behavior of those systems was revealed. Using the method of impedance spectroscopy the corresponding percolation threshold of 0.45 % was found. The critical index of conductivity t пЂЅ 1.3 was determined in the framework of McLachlan equation. The processes of charge transfer in the systems concerned were found to be described well by the proposed equivalent circuit.